INDIRECT EFFECT OF LAND COVER TOWARD ON CLOUD OPTICAL THICKNESS OVER INDONESIA - Jeddah Yanti; Togi Tampubolon; Chian Yi Liu (USN Kolaka, 2022)
The inter-relation between land surface changes (land cover) and local climate affect other atmospheric phenomenon such as clouds and their formation and properties. The Earth’s hydrological cycle is complex system describing the mutual relationship between Earth's surface and the atmospheric component, as a consequence, small changes to one part of the system can accrue to have larger effects on the other system as a whole. NDVI and cloud optical thickness obviously allocated in wet season than dry season, with fluctuated in uphill and downhill polynomial. According to wet season, downhill line of cloud optical thickness ware detected as mean value on every November during 14 years. At 1 percent of NDVI fluctuation declined two times of optical depth otherwise. Absolute result in wet season may be due to more stable and homogeneous data variability. Least sunlight for vegetation growth and the least amount of evapotranspiration energy, less cloud forms.